Habitat Potensial Gajah Sumatra (Elephas maximus sumatranus) di Resort Rawa Bunder, Seksi III Kuala Penet, Taman Nasional Way Kambas, Lampung - Subeno, Subeno; Hariyanto, Awang; Satria, Ryan Adi (Jurnal Ilmu Kehutanan, 2025)
Way Kambas National Park (WKNP) in Lampung serves as a critical habitat for the endangered Sumatran elephant (Elephas maximus sumatranus). However, the area has increasingly experienced human-elephant conflicts, particularly at the Rawa Bunder Resort. This research aimed to assess the biophysical characteristics and map the distribution of potential elephant habitats within the resort area. Field data were collected using 70 nested plots distributed along established transects and analyzed through a modified sampling protocol. An Agglomerative Hierarchical Cluster (AHC) analysis was employed to classify the habitats into suitable, moderately suitable, and less suitable categories. The georeferenced plot data were processed using ArcGIS 9.3 to create a habitat suitability map. The findings indicated that 24% of the plots were classified as suitable, 33% as moderately suitable, and 43% as less suitable. The suitable habitats were predominantly located in lowland forest areas, which represent a relatively small proportion of the total area. To expand suitable habitats and mitigate human-elephant conflicts, strategic habitat management measures, such as forest restoration and targeted enrichment, are essential. These results provide a spatial framework for conservation planning for elephant habitats in Way Kambas and other fragmented landscapes.